2019
DOI: 10.1088/1741-4326/ab443a
|View full text |Cite
|
Sign up to set email alerts
|

Improved high-performance fully non-inductive discharge by optimizing the fast-ion confinement on EAST

Abstract: The long-pulse high-performance fully non-inductive plasma is one of the major scientific objectives on EAST using the ITER-like tungsten upper divertor. Understanding and optimizing the fast-ion behaviors is the critical issue to extend the performance on EAST. Recently, using both NBI (neutral beam injection) and RF (low hybrid, electron cyclotron and ion cyclotron) heating, fully non-inductive high-β P scenarios with extension of fusion performance at high density and low rotation have been achieved with β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Other features such as a metal wall (tungsten divertor), low torque injection (T inj ∼ 1.0 Nm), electron dominated heating (T e > T i ), moderate bootstrap current fraction ( f bs ∼ 50%), broad current density profile with the central q(0) > 1.0 and good energy confinement have also been demonstrated in this scenario. Note that high-Z impurity accumulation in the plasma core was well controlled at a low level by using the on-axis ECH (P EC = 0.8 MW) from 2 s to 19 s and the fast ion losses were reduced through beam energy optimization [15]. Previous experiments in EAST have also successfully demonstrated that at higher density, the fast-ion contribution to the total plasma pressure was decreased due to reduced fast-ion slowing down time [15], which would achieve higher bootstrap fraction at the same β p level as fast ions do not contribute significantly to the bootstrap current.…”
Section: Development Of Long Pulse High Poloidal Beta Scenarios With ...mentioning
confidence: 99%
“…Other features such as a metal wall (tungsten divertor), low torque injection (T inj ∼ 1.0 Nm), electron dominated heating (T e > T i ), moderate bootstrap current fraction ( f bs ∼ 50%), broad current density profile with the central q(0) > 1.0 and good energy confinement have also been demonstrated in this scenario. Note that high-Z impurity accumulation in the plasma core was well controlled at a low level by using the on-axis ECH (P EC = 0.8 MW) from 2 s to 19 s and the fast ion losses were reduced through beam energy optimization [15]. Previous experiments in EAST have also successfully demonstrated that at higher density, the fast-ion contribution to the total plasma pressure was decreased due to reduced fast-ion slowing down time [15], which would achieve higher bootstrap fraction at the same β p level as fast ions do not contribute significantly to the bootstrap current.…”
Section: Development Of Long Pulse High Poloidal Beta Scenarios With ...mentioning
confidence: 99%
“…The experiments have been carried out with the conventional 10 s setting since the EAST NBI cannot sustain long-pulse operation at a high beam voltage (V beam > 60 kV). It should be stressed here that high density (〈n e 〉 = 4.0-5.0 × 10 19 m −3 ) was routinely used for those discharges using NBI to avoid strong shine-through loss [13]. In addition to the exploration of the high β P scenarios, extensive experiments of high β N scenario development have been carried out on EAST.…”
Section: Extension Of Steady-state Operational Regime With Dominant R...mentioning
confidence: 99%
“…The toroidal angles of the beam source for NBI1L, NBI1R, NBI2L, and NBI2R are 74.14 • , 79.41 • , −148.62 • , and −143.33 • (right-handed), respectively. The details of the NBI system can be found in reference [22]. In these discharges that show the similar tendency, the plasma is mainly heated by the two NBI systems with similar power configuration, i.e., the NBI power is stepped increased by the in-sequence injection of NBI1L, NBI1R, NBI2L and NBI2R sources.…”
Section: Resultsmentioning
confidence: 91%